Liposomes as a drug delivery system - Deen, G. Roshan; Hasan, Bushra; AlAnsari, Renad (Henry Stewart Talks, 2023)
Types of liposomes, Advantages of liposomes for drug delivery, Doxil, DaunoXome, Sterically-stabilized liposomes, Ligand-targeted liposomes, Polyethylene glycol (PEG), Challenges with liposomes